Estudo comparativo de cápsulas contendo amoxicilina obtidas de algumas farmácias magistrais - Paulo, Glauber Dias; Mazzuco, Ana Paula; Rodolpho, Juliana Cristina; Salgado, Hérida Regina Nunes [UNESP]; Moreno, Andréia de Haro (My University, 2011)
Amoxillin is a semisynthetic antibiotic classified as penicillin of wide action spectrum against gram-positive and gram-negative bacteria, largely used in the treatments of several infections. Besides, amoxicillin is a drug widely used in clinical treatment (the usual dosage is 500 mg). According to RDC n.87/2008, in order to monitoring the manipulation process, pharmacies must analyze their pharmaceutical formulations to assure some important quality parameters, such as average weight, dissolution time and assay, to guarantee the drug concentration and therapeutic efficacy. The objective of this work was to develop a comparative study of three pharmaceutic formulations containing amoxicillin 500 mg (capsules) and to compare the results to those obtained from the generic drug. The analysis was carried out according to Brazilian Pharmacopoeia for amoxicillin. Although the 3 magistral preparations analyzed have been approved in average weight determination, only one pharmaceutical formulation presented satisfactory results for time dissolution and assay determinations (81,30 ± 0,98% and 91,65 ± 0,72%, respectively). The results showed the necessity of a strict quality monitoring by the pharmacies to assure the correct drug dosage and its therapeutic efficacy. The selection of excipients and the weight, blend and encapsulation procedures are very important, as well as the evaluation of the purity and integrity of raw materials.

A amoxicilina é um antibiótico semissintético pertencente à classe das penicilinas, ativo contra bactérias grampositivas e gram-negativas, empregado no tratamento de diversas infecções, sendo um dos fármacos mais utilizados na antibioticoterapia (dose usual de 500 mg). De acordo com a RDC n.o 87/2008, as farmácias devem analisar seus produtos terminados, a fim de assegurar alguns parâmetros de qualidade essenciais, tais como peso médio, tempo de dissolução e teor de princípio ativo. O objetivo do presente trabalho foi realizar o estudo comparativo de três preparações magistrais contendo amoxicillin 500 mg (cápsulas) e comparar os resultados com aqueles obtidos com o medicamento genérico. A metodologia utilizada foi a preconizada pela Farmacopeia Brasileira para amoxicilina. Das três preparações magistrais analisadas, todas foram aprovadas quanto ao peso médio, porém apenas uma apresentou conformidade com o tempo de dissolução e com o teor (81,30 ± 0,98% e 91,65 ± 0,72%, respectivamente). Os resultados indicaram a necessidade de um monitoramento rigoroso por parte das farmácias magistrais, a fim de assegurar a correta dose do fármaco e a eficácia terapêutica, na escolha dos excipientes e dos procedimentos corretos de pesagem, homogeneização e encapsulação, bem como a avaliação da pureza e integridade das matérias-primas.
Keywords: Amoxicillin capsules; Pharmacies; Quality control; Cápsulas de amoxicilina; Farmácias magistrais; Controle de qualidade